Proposal for a model for measuring intellectual capital that allows diagnosing its influence on the competitiveness of Tacna's agro-export companies - Arámbulo Ayala, Marizol Candelaria (2013)
Objective: Propose a model for measuring intellectual capital that enables diagnose their influence on the competitiveness of agribusiness firms-exporters Tacna. Method: Review of the various approaches about intellectual capital and competitiveness, which enabled a methodology based on the indicators proposed for measurement. Due to the nature of the research, the questionnaire is presented as the most appropriate tool for specific information. Few studies have addressed intellectual capital in full, so that is selected and integrated measurement indicators from various sources, we have designed a series of questions related to the variables where as the number of questions it is suitable for that application. Functions were performed typical data processing flow; we applied exploratory factor analysis to each of the measurement scales of the model, with their respective tests and statistical measures, which resulted in the identification of the factors of each component with its respective factor loadings. Additionally, regression analysis was used to diagnose the behavior of competitiveness from intellectual capital. Result: The measurement models 24 scale indicators for intellectual capital, and 9 to competitiveness, and it is found that the set of intellectual capital assets have a positive influence on competitiveness. Conclusions: Results have been allowed confirm in the strategic value of intellectual capital and its connection with competitiveness.